THE EFFECT OF COVID-19 AND SECTORAL FINANCING ON ISLAMIC BANK PROFITABILITY IN INDONESIA - Fajri, Mohammad Zen Nasrudin; Muhammad, Adamu Abu Bakar; Umam, Khoirul; Putri, Lila Prisilia; Ramadhan, Mohammad Ali (Journal of Islamic Economic Laws, 2022)
COVID-19 pandemic has created a new economic crisis worldwide. Islamic Bank which was reportedly resilient against the financial crisis is expected to be stable in this period. Apart from that, Islamic Bank in Indonesia has channeled financing fund to various business sectors with different portions leading to a question whether they have different impact on Islamic Bank’s profitability. This paper aims to discover the impact of COVID-19 pandemic and financing to business sectors on Islamic Bank profitability in Indonesia. An ARDL approach is employed for analysis. The result of the study shows that COVID-19 pandemic has a negative relationship with Islamic Bank profitability in the long-run. Furthermore, financing to transportation, warehousing and communication sectors is associated with higher profitability in the short-run. On the other hand, financing to wholesale and retail trade sectors hurt Islamic Bank profitability. Based on this result, it is suggested that Government impose some measures in stabilizing Islamic Bank’s performance during COVID-19 pandemic. In addition, Islamic Banks are expected to make adjustment on financing to business sectors ratio accordingly in order to maintain the profitability of Islamic Bank.